Electronic skin technologies: From hardware building blocks and tactile sensing to control algorithms and applications - Elisabetta Leogrande; Mariangela Filosa; Sara Ballanti; Luca De Cicco; Stefano Mazzoleni; Rochelle Ackerley; Calogero Oddo; Francesco Dell’Olio (Sensors and Actuators Reports, 2025)
E-skin technologies are poised to reshape numerous sectors, offering new possibilities through their thin, flexible, and highly sensitive interfaces. By integrating advanced transducer mechanisms and edge artificial intelligence computing, these interfaces not only enhance the quality of services and products but also promote greater user interaction and real-time data processing. Prosthetic and rehabilitation devices equipped with human-machine interfaces can improve the lives of people with disabilities, enabling them to interact more naturally with their environment. Furthermore, recent studies and advanced sensors have achieved sensitivity and accuracy levels not only comparable to human tactile receptors but even superior, enabling unprecedented touch perception and interaction. In the field of robotics, e-skins provide robots with human-like tactile sensitivity, enhancing their efficiency and safety when interacting with humans, machines, and the environment. The integration of e-skins with soft robotics and edge AI technology opens new frontiers in device design, making them more adaptable and capable of dynamically responding to user needs. Recent advances in flexible interfaces have led to improved transducer sensitivity and energy-efficient processing, ensuring better integration with wearable devices and interactive systems. These developments highlight the growing emphasis on real-time data processing and adaptive learning algorithms, key to the future of human-machine interactions. This paper delves into the materials, structures, and mechanisms that constitute flexible electronic interfaces and their applications. Progress and challenges in implementing effective human-machine interfaces are examined. The paper concludes with a discussion on the prospects and current challenges in the field of human-machine interfaces, particularly in medical robotics.
Keywords: Electronic skin; Flexible sensors; Microfabrication; Strain sensors; Collaborative robots; Artificial intelligence